Environmental regulation, asymmetric information and foreign ownership - Jon Vislie (University of Oslo, Department of Economics, 2001)
Regulating an export firm (or a homogeneous industry) with private information about emission technology is analysed, when the firm, owned partly by foreigners, has an option to bypass domestic regulation through costly relocation. If the firm chooses to relocate, it will set up a new plant in a region practicing environmental dumping, at a cost that is correlated with emission efficiency, so as to make the firm's reservation utility type-dependent. We characterise the set of optimal contracts offered by the uninformed, domestic government under different ownership structures, when domestic taxation is distortive, and when welfare is the sum of consumers' surplus and the share of the firm's rent accruing to domestic residents. With complete information, ownership has no real effects. When information is incomplete, ownership matters, due to rent extraction, being of greater significance when ownership rights are shifted towards foreigners. Rent extraction is accomplished by offering contracts with lower output and higher net emissions to a subset of the most efficient types (being induced to stay), whereas a subset of the least efficient types should be induced to relocate. A demand for environmental dumping is being induced by the domestic government's concern for national interests. When barriers towards foreign ownership are lowered, and then shifting the distribution of ownership rights in the favour of foreigners, more pollution will be generated for types of the firm that do not exit, whereas a larger fraction of the firm types should be induced to relocate.
Keywords: D62; D82; H23; L51; 330; Asymmetric information; environmental regulation; foreign ownership; Asymmetrische Information; Umweltpolitik; Theorie der Regulierung; Eigentümerstruktur; Betriebliche Standortwahl; Theorie